Proceedings of the 2017 CHI Conference on Human Factors in Computing Systems 2017
DOI: 10.1145/3025453.3025614
|View full text |Cite
|
Sign up to set email alerts
|

Multi-moji

Abstract: This paper explores the combination of multiple concurrent modalities for conveying emotional information in HCI: temperature, vibration and abstract visual displays. Each modality has been studied individually, but can only convey a limited range of emotions within two-dimensional valencearousal space. This paper is the first to systematically combine multiple modalities to expand the available affective range. Three studies were conducted: Study 1 measured the emotionality of vibrotactile feedback by itself;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Most touch devices used vibration motors to generate the touch stimuli. For example, Multi-Moji [50] used the built-in vibration motors in smartphones to enhance emojis with tactile feedback. TaSSt [24] and VisualTouch [53] used vibration motor arrays embedded on a tactile sleeve to generate tactile patterns on forearms.…”
Section: Designing Mediated Touch Devicesmentioning
confidence: 99%
See 4 more Smart Citations
“…Most touch devices used vibration motors to generate the touch stimuli. For example, Multi-Moji [50] used the built-in vibration motors in smartphones to enhance emojis with tactile feedback. TaSSt [24] and VisualTouch [53] used vibration motor arrays embedded on a tactile sleeve to generate tactile patterns on forearms.…”
Section: Designing Mediated Touch Devicesmentioning
confidence: 99%
“…Combining touch with other modalities could also expand the available range of emotional states and increase the touch perception [43,50,53]. For example, Wilson et al [50] showed that combining visual and thermal modalities in touch interactions allowed users to convey a wider range of afective expressions.…”
Section: Designing Mediated Touch Devicesmentioning
confidence: 99%
See 3 more Smart Citations